The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/htj.21834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diethyl ether additive in Jatropha biodiesel‐diesel fuel blends on the variable compression ratio diesel engine performance and emissions characteristics at different loads and compression ratios

Abstract: An investigational analysis was performed to assess the effect of diethyl ether (DEE) that acts as an oxygenated additive in Jatropha biodiesel and diesel fuel blends on the performance enhancement and emission reduction of a variable compression ratio (CR) diesel engine. The DEE (10% vol) is added to different concentration levels of Jatropha biodiesel (B5, B10, and B20). The Jatropha biodiesel (JME) is prepared by the transesterification reaction and DEE is prepared through acid distillation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(110 reference statements)
0
0
0
Order By: Relevance
“…These unexpected increases in CO may be attributed to the poor air/biodiesel mixing or atomization. The highest reduction of 60% was found in case of 10% iso-butanol and 10% di-ethyl ether blends with Calophyllum inophyllum and Neem biodiesel, respectively [108,126]. It was also found that a Calophyllum inophyllum biodiesel blend even without oxygenated additives, due to it containing a higher oxygen content, showed a significant reduction in CO emissions compared to other second-generation biodiesel blends.…”
Section: Effect On Carbon Monoxide Emissionmentioning
confidence: 89%
“…These unexpected increases in CO may be attributed to the poor air/biodiesel mixing or atomization. The highest reduction of 60% was found in case of 10% iso-butanol and 10% di-ethyl ether blends with Calophyllum inophyllum and Neem biodiesel, respectively [108,126]. It was also found that a Calophyllum inophyllum biodiesel blend even without oxygenated additives, due to it containing a higher oxygen content, showed a significant reduction in CO emissions compared to other second-generation biodiesel blends.…”
Section: Effect On Carbon Monoxide Emissionmentioning
confidence: 89%